Prinsip Estetika Pakaian Cosplay Yogyakarta: Fantasi dan Ekspresi Desain Masa Kini - Setiawan, Deni; Haryono, Timbul; Burhan, M. Agus (PANGGUNG, 2014)
ABSTRACTCostume, dress code, animation, comics, legends, and manga, are inseparable parts of the cosplay costume. Those parts give fantasy and digital world discourse through costume style. Its spiritual domain stands on Japanese culture by being cultured through clothing. One of them, cosplay ideo- logy, reflects the self-imaging through social communities, as an e?ort for group and self-existence. Cosplay entity bridges fantasy and real world, presents designersâ expressions through the costume designs to show. This writing will be analyzed by using the main theories based on Dewitt H. Parker point of view, in The Principles of Aesthetics, which divides principles of aesthetics into three, they are: Principle of Organic Unity, Principle of Dominant Element, and Principle of Balance. Principle of organic unity indicates that cosplay clothing is an accumulation of design elements, to refer and mark a figure. Principle of dominant element, is accentuation, or the center of interest of a cosplay clothing design. Principle of balance, see placement and setting ornamentation applied to cosplay clothing.Keywords: cosplay clothing, principles of aesthetics, costume style, YogyakartaABSTRAKPakaian, dress code, animasi, dan manga, merupakan unsur yang tidak terpisahkan dalam pakaian cosplay. Unsur-unsur tersebut merupakan wacana dunia digital dan fantasi pada dunia pakaian. Ranah spiritualnya berp?ak pada kebudayaan Jepang yang dibudayakan melalui pakaian. Ideologi cosplay salah satunya menggambarkan pencitraan diri komuni- tas sosial, sebagai usaha untuk aktualisasi diri. Entitas cosplay mampu menjembatani du- nia fantasi dan realita, yang membelenggu keinginan manusia untuk bergaya. Tulisan ini akan dianalisis dengan teori pokok berdasarkan pandangan Dewitt H. Parker, dalam The Principles of Aesthetics, yang membagi prinsip estetika menjadi tiga, yaitu: prinsip kesatu- an organik, prinsip unsur dominan, dan prinsip keseimbangan. Prinsip kesatuan organik menunjukkan, bahwa pakaian cosplay merupakan akumulasi dari unsur-unsur desain, un- tuk merujuk dan menandai tokoh. Prinsip unsur dominan, merupakan aksentuasi, atau pusat perhatian dari sebuah desain pakaian cosplay. Prinsip keseimbangan, melihat penem- patan dan pengaturan ornamentasi yang diaplikasikan pada pakaian cosplay.Kata kunci: pakaian cosplay, prinsip estetika, gaya pakaian, Yogyakarta